Transport Correlation and Structural Defects (Advances in Disordered Semiconductors) - Fritzche Hellmut (World Scientific, 1990)
"The different points of view on the problems of the field are evident in this work and add to the interest of the book ... The ideas are frequently speculative, making for stimulating and enjoyable reading.